Analysis of methods for increasing the production of rapeseed oilseeds and their environmental component - Lamanos, Volha; Lamanos, Mikhail (Journal of the Belarusian State University. Ecology, 2025)
The article analyzes the main trends and features of the production of rapeseed oilseeds (winter and spring) in the context of its key components for the period 2019–2023. The results of a comparative analysis of statistical data from the National Statistical Committee of the Republic of Belarus for a five-year period on the area of rapeseed and the level of its productivity, as well as the volume of mineral fertilizers applied to this crop are presented. Taking into account the analyzed scientific information, a promising, environmentally safe and economically viable way to further increase the gross harvest of rapeseed oilseeds by expanding the acreage directly under rapeseed hybrids is proposed. In the republic during 2019–2023. There is an increase in the area under winter and spring rapeseed. The area of rapeseed during the study period increased by 71 thousand hectares and in 2023 amounted to 495 thousand hectares with a specific weight in the structure of crops of 8.6%. An increase in the gross harvest of rapeseed to 863 thousand tons is also noted due to an increase in the amount of mineral fertilizers used by 35%, reaching a level of 329 kg/ha a.i. NPK. As a result of the analysis of the yield of rapeseed oilseeds depending on the proportion of hybrids in the structure of sown areas, a reliable correlation was established between an increase in yield from 16.8 to 23.2 dt/ha as the share of hybrids used for sowing increased from 24% in 2019 to 49% in 2023. Cultivation of hybrids of winter and spring rape allows saving nitrogen fertilizers due to their effective use by modern hybrids. The level of savings can be about 7–8 kg/ha a.i. nitrogen or 17.2–19.6 Belarusian rubles per 1 ha in monetary terms at prices as of November 1, 2024.
Keywords: winter and spring rapeseed; productivity; mineral fertilizers; rapeseed hybrids; ecology; environment